2023
DOI: 10.1037/xge0001445
|View full text |Cite
|
Sign up to set email alerts
|

Body appearance values modulate risk aversion in eating restriction.

Paul Mark Jenkinson,
Athanasios Koukoutsakis,
Elena Panagiotopoulou
et al.

Abstract: The understanding of eating disorders is hindered by the lack of integration between existing psychosocial and neurobiological approaches. We address this problem by developing a novel transdiagnostic and computational approach to eating restriction decisions. We first validated a novel paradigm which extends an established monetary risk task to involve body stimuli with psychosocial values. We used advanced behavioral data analysis of a large (total N = 539) sample of women from across the eating restraint sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 70 publications
4
9
0
Order By: Relevance
“…By contrast, increasing age predicts fewer balloon pumps (b = -0.34, p =.006, 95% CI [-0.59--0.10]; R 2 Marginal Increment = 0.011). Eating disorder symptoms, while not statistically significant, showed an effect direction consistent with our previous research looking at eating restraint [23], such that increasing eating disorder symptoms predicts a decrease in pumping (b = -1.21, p =.112, 95% CI [-2.71-0.28]; R 2…”
Section: Bart Performancesupporting
confidence: 84%
“…By contrast, increasing age predicts fewer balloon pumps (b = -0.34, p =.006, 95% CI [-0.59--0.10]; R 2 Marginal Increment = 0.011). Eating disorder symptoms, while not statistically significant, showed an effect direction consistent with our previous research looking at eating restraint [23], such that increasing eating disorder symptoms predicts a decrease in pumping (b = -1.21, p =.112, 95% CI [-2.71-0.28]; R 2…”
Section: Bart Performancesupporting
confidence: 84%
“…Participants responded to advertisements posted on message boards, social media, email and a university research participant pool (SONA). They were aged 18 years or above with a BMI [16.5 [consistent with a lower average observed in similar studies of this student population; see [23], and no reported history of eating disorder, neurological disease, or brain damage. Exclusion criteria were a history of psychiatric illness, substance abuse or dependency, or a firstdegree relative with an eating disorder].…”
Section: Participantssupporting
confidence: 79%
“…In recent research involving women with restrictive eating (including women with anorexia nervosa), we found that body-based stimuli with high social-motivational salience (i.e. images of women of varying degrees of 'thinness') moderated risktaking behaviour, with greater risk taking observed in women with greater restrictive eating when decisions were linked to an thinner versus a larger body [23]. An interesting area for future research would be to examine whether cosmetic surgery-related risk taking is even greater when the potential reward is obtaining their ideal body after surgery, such as when specific, desired body modifications (e.g.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…AN patients met the restrictive subtype AN DSM-5 criteria (American Psychiatric Association, 2013) as diagnosed by an experienced clinician using standard clinical measures (patient history, psychometric questionnaires and a physical assessment), and had a BMI<18.5. Given growing concerns around weight-restoration criteria (e.g., (Harrop et al, 2021;Khalsa et al, 2017;Lebow et al, 2018;Ralph et al, 2022), we chose a combination of objective and clinical criteria to best represent the patients' clinical reality (see also (Jenkinson et al, 2023)) instead of relying only on BMI criteria, as it inadequately reflects the clinical complexity of the AN recovery stages and symptom evolution. The AN-WR group no longer met DSM-5 restrictive subtype AN criteria according to their psychiatrist and met at least two of the following: BMI >16.5, clinical and behavioural signs of AN recovery (e.g., no restrictive eating patterns) for at least 6 months, and/or a global Eating Disorders Examination Questionnaire (EDE-Q; (Fairburn & Beglin, 1994)) score <4.…”
Section: Participantsmentioning
confidence: 99%